2020
DOI: 10.1002/advs.202002602
|View full text |Cite
|
Sign up to set email alerts
|

Protein Arginine Methyltransferase PRMT5 Regulates Fatty Acid Metabolism and Lipid Droplet Biogenesis in White Adipose Tissues

Abstract: The protein arginine methyltransferase 5 (PRMT5) is an emerging regulator of cancer and stem cells including adipogenic progenitors. Here, a new physiological role of PRMT5 in adipocytes and systemic metabolism is reported. Conditional knockout mice were generated to ablate the Prmt5 gene specifically in adipocytes (Prmt5 AKO). The Prmt5 AKO mice exhibit sex-and depot-dependent progressive lipodystrophy that is more pronounced in females and in visceral (than subcutaneous) white fat. The lipodystrophy and asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 73 publications
0
26
0
Order By: Relevance
“…Meanwhile, the interaction between LSD1 and snail family transcriptional repressor 2 (SNAIL2, also known as SLUG, an important epigenetic regulator of de novo adipose tissue) mediates the demethylation of H3K9 and stimulates FASN expression and lipogenesis Manuel and Haeusler, 2020). Protein arginine methyltransferase 5 (PRMT5) regulates fat cells by promoting the expression of fatty acid synthase (FASN; lipid synthesis gene) by methylating sterol regulatory element binding transcription factor 1 (SREBP1) (Jia et al, 2020).…”
Section: Histone Modificationsmentioning
confidence: 99%
“…Meanwhile, the interaction between LSD1 and snail family transcriptional repressor 2 (SNAIL2, also known as SLUG, an important epigenetic regulator of de novo adipose tissue) mediates the demethylation of H3K9 and stimulates FASN expression and lipogenesis Manuel and Haeusler, 2020). Protein arginine methyltransferase 5 (PRMT5) regulates fat cells by promoting the expression of fatty acid synthase (FASN; lipid synthesis gene) by methylating sterol regulatory element binding transcription factor 1 (SREBP1) (Jia et al, 2020).…”
Section: Histone Modificationsmentioning
confidence: 99%
“…Interestingly, PRMT5 has been reported to play a role in metabolic pathways that perpetuate the pathologies of T2DM. For instance, in white adipose tissue, PRMT5 methylates sterol regulatory element-binding transcription factor 1a (SREBP1a) to enhance triacylglycerol formation [67]. PRMT5 also methylates the transcription elongation factor SPT5 to promote lipid droplet biogenesis [67].…”
Section: Prmt5 In Diabetesmentioning
confidence: 99%
“…For instance, in white adipose tissue, PRMT5 methylates sterol regulatory element-binding transcription factor 1a (SREBP1a) to enhance triacylglycerol formation [67]. PRMT5 also methylates the transcription elongation factor SPT5 to promote lipid droplet biogenesis [67]. A separate study also reported that PRMT5 serves as a coactivator for the expression of adipogenic genes, such as peroxisome proliferator-activated receptor γ2 (PPARγ2), adipocyte protein 2 (aP2), adiponectin, leptin, and resistin [68].…”
Section: Prmt5 In Diabetesmentioning
confidence: 99%
“…Available reports have demonstrated the role of PRMT5 in regulating lipid biogenesis. Notably, PRMT5 arbitrates seipin-mediated lipid droplet biogenesis in adipocytes (23). Besides, PRMT5 could enhance lipogenesis in cancer cells by methylating SREBP1a (24).…”
Section: Introductionmentioning
confidence: 99%